Analysis of Decision-Making Techniques in Increasing MSMEs Reviewed from a Managerial Economic Perspective (Study of MSEMs in Jombang Regency) - Kholifah, Siti (LPPM Universitas KH. A. Wahab Hasbullah, 2024)
In the dynamic era of the business world, every company or UMKM actor is required to be able to have the ability to make decisions and choose the right decision-making techniques within the wheels of an organization or company, especially for a leader or manager. Therefore, researchers conducted this research using the literature study method to see how effective decision-making techniques can be used for MSME actors in terms of the perspective of Managerial Economics.